Marker Placement Reliability and Objectivity for Biomechanical Cohort Study: Healthy Aging in Industrial Environment (HAIE-Program 4) - Malus, Jan; Skypala, Jiri; Silvernail, Julia Freedman; Uchytil, Jaroslav; Hamill, Joseph; Barot, Tomas; Jandacka, Daniel (Sensors (Basel, Switzerland), 2021)
In large cohort studies, due to the time-consuming nature of the measurement of movement biomechanics, more than one evaluator needs to be involved. This may increase the potential occurrence of error due to inaccurate positioning of markers to the anatomical locations. The purpose of this study was to determine the reliability and objectivity of lower limb segments length by multiple evaluators in a large cohort study concerning healthy aging in an industrial environment. A total of eight evaluators performed marker placements on five participants on three different days. Evaluators placed markers bilaterally on specific anatomical locations of the pelvis, thigh, shank and foot. On the right foot, markers were placed in anatomical locations to define a multi-segmental foot model. The position of the marker at the anatomical locations was recorded by a motion capture system. The reliability and objectivity of lower limb segment lengths was determined by the intraclass correlation coefficient of a two-way random model and of the two-way mixed model, respectively. For all evaluators for all segments, the average reliability and objectivity was greater than 0.8, except for the metatarsus segment (0.683). Based on these results, we can conclude that multiple evaluators can be engaged in a large cohort study in the placement of anatomical markers.
Keywords: Reproducibility of Results; standard error of measurement; multi-segment foot model; minimal detectable change; lower limb; biomechanika; kohortové studie; Biomechanical Phenomena; Gait; lidé; chůze (způsob); optoelectronic stereophotogrammetry; Humans; Cohort Studies; Healthy Aging; reprodukovatelnost výsledků; zdravé stárnutí